1985
DOI: 10.1128/aac.27.2.197
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity studies on phosphonoacetate

Abstract: Phosphonoacetic acid is a selective antiherpesvirus agent. More than 100 congeners of phosphonoacetic acid were evaluated in vitro and in vivo to understand structure-activity relationships in the hope of designing a superior analog. Results showed that the antiherpesvirus activity had highly specific structural requirements. Neither the carboxylic nor the phosphono groups could be replaced. The distance between these two groups is important. Increase of this distance caused complete loss of activity. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…1) (12, 13). For the nonencapsulated compounds, the EC50s for both PA (60 ± 25 ,uM) and PF (210 ± 85 ,uM) were consistent with previously published values (PA = 60 to 100 ,uM and PF = 60 to 200 ,uM) against various strains of HSV (8,14,15,20,22,23,24). Thus, the increase in efficacy of the liposome-encapsulated compounds (PA = 0.4 p.M, PF = 7 ,uM) could be important for in vivo antiviral activity of PA and PF.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…1) (12, 13). For the nonencapsulated compounds, the EC50s for both PA (60 ± 25 ,uM) and PF (210 ± 85 ,uM) were consistent with previously published values (PA = 60 to 100 ,uM and PF = 60 to 200 ,uM) against various strains of HSV (8,14,15,20,22,23,24). Thus, the increase in efficacy of the liposome-encapsulated compounds (PA = 0.4 p.M, PF = 7 ,uM) could be important for in vivo antiviral activity of PA and PF.…”
Section: Discussionsupporting
confidence: 77%
“…The pKaS of the three titratable groups of PF are 7.3, 3.4, and 0.5 (34), while the analogous values for PA are 8.2, 5.0, and 2.6 (20). The poor penetration can be attributed to the multianionic nature of the phosphono compounds at physiological pH.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This result prevented clinical studies from being performed with PAA. Structureactivity studies have been reported for 100 analogues of PAA, but all analogues were less active than PAA [300].…”
Section: Phosphonoacetate and Phosphonoformatementioning
confidence: 99%
“…, although excep tions have been reported (16.17). Prior studies of PAA-like com pounds (15)(16)(17)(18)(19)(20) provide evidence that one phosphonate group, in close proximity (preferably one or zero intervening atoms) to a carboxylate, is associated with activity. Replacement of the carboxylate group in 2a by a phosphonate group (methanediphosphonic acid/methylene bis [phosphonic acid], MDP, 3a) resulted in loss of activity (18) .…”
Section: Pyrophosphate Analoguesmentioning
confidence: 99%